Distinct mechanisms of electroacupuncture and manual acupuncture in modulating hypothalamic GnRH–tanycyte unit function of polycystic ovary syndrome - Yu Wang; Yicong Wang; Yuning Chen; Wenhan Lu; Xiaoyu Tong; Jiajia Li; Wenhao Gao; Rui Huang; Wei Hu; Yi Feng (Chinese Medicine)
Abstract Background Polycystic ovary syndrome (PCOS) is a complex neuroendocrine disorder characterized by dysregulation of the hypothalamus. Both electroacupuncture (EA) and manual acupuncture (MA) have demonstrated therapeutic efficacy in the treatment of PCOS through improvements in hypothalamic function. However, the underlying mechanisms remain poorly understood. Gonadotropin-releasing hormone (GnRH) neurons are pivotal in regulating hypothalamic endocrine function, whereas tanycyte, a specialized glial cell type, potentially contribute to this process. Methods A dihydrotestosterone (DHT)-induced PCOS-like mouse model was used to investigate the effects of acupuncture. Tissue clearing and three-dimensional (3D) imaging were employed to visualize the hypothalamic GnRH neuronal network and assess postacupuncture modifications. Transcriptome sequencing was performed to identify changes in the gene profiles associated with EA and MA. Rax-CreERT2 transgenic mice were utilized to investigate the molecular targets of EA in tanycytes. Results EA significantly alleviated neuroendocrine dysfunction in PCOS-like mice by restoring the density and coverage of GnRH axonal projections. MA displayed similar therapeutic effects but had less pronounced effects on GnRH axons. Transcriptome analysis revealed distinct mechanisms for these two approaches: EA primarily regulates neuroglial plasticity, whereas MA predominantly targets neurotransmitter regulation. Both EA and MA share a common therapeutic target in the integrin family. Functional studies in Rax-CreERT2 transgenic mice confirmed that Itgb1 plays a critical role in maintaining the balance of hypothalamic GnRH–tanycyte unit during EA treatment. Conclusions EA exerts therapeutic effects on PCOS by targeting hypothalamic GnRH–tanycyte unit, with Itgb1 identified as a key factor. MA primarily functions through neurotransmitter regulation. These findings highlight potential hypothalamic targets and provide new insights into the distinct mechanisms of EA and MA.